The Epidemiology of Revision Anterior Cruciate Ligament Reconstruction in Ontario, Canada. (November 2014) - Leroux, Timothy; Wasserstein, David; Dwyer, Tim; Ogilvie-Harris, Darrell J.; Marks, Paul H.; Bach, Bernard R.; Townley, John B.; Mahomed, Nizar; Chahal, Jaskarndip
Background: Knowledge of the rate of and risk factors for re-revision, reoperation, and readmission after revision anterior cruciate ligament reconstruction (ACLR) is limited. Purpose: To determine the rate of and risk factors for re-revision, reoperation, and readmission after revision ACLR. Study Design: Descriptive epidemiology study. Methods: All patients who underwent first revision ACLR in Ontario, Canada, from January 2004 to December 2010 were identified and followed until December 2012. Exclusions included age <16 years, previous osteotomy, or multiligament knee reconstruction. The main outcome was re-revision ACLR. Secondary outcomes included reoperation (irrigation and debridement [I&D], meniscectomy, manipulation under anesthesia, contralateral ACLR, and total knee arthroplasty) and readmission. Survival to re-revision was determined using the Kaplan-Meier approach. A Cox proportional hazards model or logistic regression were used to determine the influence of patient, surgical, and provider factors on outcomes. A post hoc analysis was performed to determine the influence of the aforementioned factors on postoperative infection risk. Results: Overall, 827 patients were included (median age, 30 years; 58.8% males). Single-stage revisions comprised 92.9% of cases, and a meniscal procedure (repair or debridement) was performed in 45.3% of cases. The re-revision rate at a mean follow-up of 4.8 ± 2.2 years was 4.4%, and the 5-year survival rate was 95.4%. The rates of I&D, meniscectomy, contralateral ACLR, and readmission were 0.8%, 3.1%, 3.4%, and 4.1%, respectively. Manipulation under anesthesia and total knee arthroplasty were rare. Young age significantly increased contralateral ACLR risk (risk decreased by 5.1% with each year of age >16 years; P = .02) but not re-revision ACLR risk. Low surgeon's annual volume of revision ACLR (<4 revisions/year: odds ratio, 1.2; P = .02) and male sex (odds ratio, 13.3; P = .01) significantly increased overall infection risk; male sex also influenced I&D risk. Conclusion: Re-revision, reoperation, and readmission rates after revision ACLR were low, and the risk for I&D, infection, and contralateral ACLR were influenced by male sex, low surgeon volume, and young age, respectively. Clinical Relevance: This is the first study to determine morbidity rates and risk factors after revision ACLR, providing reference data from the general population.